Stephanine interacts with TNF-α to block NF-κB signaling and protects against rheumatoid arthritis - Titi Liu; Meiyan Duan; Jin Li; Wei Dong; Yingqi Yin; Honglei Hui; Jing Xu; Zhe Jiang; Chunxia Gan; Zemin Xiang; Jun Sheng; Xuanjun Wang; et al. (Food Science and Human Wellness)
Tumor necrosis factor-α (TNF-α) is a key player in the pathogenesis of rheumatoid arthritis (RA) and considered a promising target for therapeutic drug development. Activation of the nuclear factor-kappa B (NF-κB) pathway upon TNF-α binding to its receptor is crucial for progression of RA. Stephanine (SA), an isoquinoline aporphine-type alkaloid recently identified in Stephania plants, exhibits anti-inflammatory properties, but its underlying mechanisms of action are unknown at present. In this study, we explored whether SA could ameliorate RA through inhibition of the NF-κB signaling pathway in association with TNF-α activity. Our experiments revealed a binding affinity (KD) of SA for TNF-α of 2.934 × 10−6 mol/L. Additionally, SA at a concentration of 10 μmol/L effectively hindered the binding of TNF-α to its receptors tumor necrosis factor receptor 1 (TNFR1) and TNFR2. In vitro, SA prevented TNF-α-induced death of L929 cells and blocked NF-κB activation triggered by TNF-α in 293-TNF-α responsive, as well as human fibroblast-like synoviocytes (HFLS) and human RA fibroblast-like synoviocytes (MH7A) cell lines. Furthermore, in a collagen-induced arthritis (CIA) mouse model, SA alleviated the symptoms of RA through suppression of NF-κB signaling. Our collective findings support the therapeutic efficacy of SA, a natural compound targeting TNF-α, in the management of RA.